Photocatalytic degradation of methylene blue using ZnO supported on wood waste-derived activated carbon (ZnO/AC) - Loke, J.Y.; Ros Shazuin Rayyanu, Mohd Zaki; Setiabudi, Herma Dina (Elsevier Ltd, 2022)
This study reports the preparation of ZnO supported on wood waste-derived activated carbon (ZnO/AC) and its activity towards photocatalytic degradation of methylene blue (MB). The removal of MB is imperative owing to its toxic impacts on the receiving water bodies. Thus, finding treatment techniques with criteria of efficient, cost-effective, and environmentally benign is highly needed. ZnO/AC has been synthesized by the incipient wetness impregnation method and was characterized using XRD, FTIR, PL, and UV–Vis-NIR. Characterization analysis revealed the successful impregnation of ZnO onto the AC. The best photocatalytic degradation of MB using ZnO/AC was achieved at 180 min, adsorbent dosage of 3 g/L, and pH8. Complete MB degradation was attained at lower initial MB concentrations (10 – 50 mg/L) and slightly decreased at higher initial MB concentration (100 mg/L). The experimental data fitted well with the pseudo-first-order Langmuir-Hinshelwood kinetic model with a correlation coefficient (R2) greater than 0.995. The results revealed that the synthesized ZnO/AC exhibited remarkable photocatalytic activity towards the degradation of MB.